2023
DOI: 10.1021/acs.nanolett.3c01023
|View full text |Cite
|
Sign up to set email alerts
|

Two-Pronged Microbe Delivery of Nitric Oxide and Oxygen for Diabetic Wound Healing

Abstract: Chronic inflammation and hypoxia in the microenvironment of diabetic foot ulcers (DFUs) can result in sustained vascular impairment, hindering tissue regeneration. While both nitric oxide and oxygen have been shown to promote wound healing in DFUs through anti-inflammatory and neovascularization, there is currently no available therapy that delivers both. We present a novel hydrogel consisting of Weissella and Chlorella, which alternates between nitric oxide and oxygen production to reduce chronic inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Healing diabetic wounds presents challenges, with the prolonged hypoxic environment, unresolved inflammation during the inflammatory phase, and reduced angiogenesis in the proliferative phase being significant contributing factors. ,, Previous studies have demonstrated that HIF-1α in wounds stimulates angiogenesis, fibroblast proliferation, and migration, thereby promoting effective wound healing . Hyperglycemia’s inhibitory impact on HIF-1α stabilization is a pivotal factor in the delayed healing observed in diabetic wounds, leading to persistent hypoxia on the wound surface.…”
Section: Discussionmentioning
confidence: 99%
“…Healing diabetic wounds presents challenges, with the prolonged hypoxic environment, unresolved inflammation during the inflammatory phase, and reduced angiogenesis in the proliferative phase being significant contributing factors. ,, Previous studies have demonstrated that HIF-1α in wounds stimulates angiogenesis, fibroblast proliferation, and migration, thereby promoting effective wound healing . Hyperglycemia’s inhibitory impact on HIF-1α stabilization is a pivotal factor in the delayed healing observed in diabetic wounds, leading to persistent hypoxia on the wound surface.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrogel alternately produces nitric oxide and O 2 , reducing chronic inflammation and hypoxia. 171 It is worth noting that in addition to the important role of oxygen in diabetes wounds, other gas molecules such as hydrogen, carbon monoxide, hydrogen sulfide, etc. have shown beneficial therapeutic effects on diabetic wounds.…”
Section: Smart Hydrogels For Wound Therapymentioning
confidence: 99%
“… 61 Based on gas therapy, a novel hydrogel comprising Weissella and Chlorella vulgaris was utilized for treating diabetic wounds of mice, which alternated the production of nitric oxide and oxygen to reduce inflammatory response and hypoxia while promoting vascular regeneration and tissue repair processes. 147 In addition to incorporating substances that promote vascularization, the development of angiogenic hydrogels can involve the inclusion of various forms of angiogenic factors into the hydrogel matrix. For instance, Yu et al 63 incorporated VEGF-encapsulated activated neutrophil exosome mimetics into an ECM-based hydrogel to create a hybrid biomaterial for targeted delivery of VEGF, ultimately promoting angiogenesis and accelerating the regeneration of diabetic wounds ( Figure 6(d) ).…”
Section: The Complex Microenvironment Of Diabetic Wounds and The Cust...mentioning
confidence: 99%